Nadania obywatelstwa rzymskiego w Hiszpanii w okresie wojny sertoriańskiej = The granting of the Roman citizenship in Spain during the Sertorian War - Ładoń, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the years 80-71 BC in Spain played out a fierce war between the rebellious Marian governor, Quintus Sertorius, and Senate commanders, Q . Metellus Pius and Cn. Pompeius. An important issue for both sides during this conflict was to gain sympathy of local peoples and one of the elements of such a policy was giving the Roman citizenship to the population of the province. In the first part of the article the author considers the possibility of granting the Roman citizenship by Sertorius to representatives of the Spanish aristocracy.
Keywords: civitas Romana; Wojna sertoriańska (80-71 p. n.e.)